Hubungan Work-life Balance dan Psychological Well-being Pada Atlet E-sports - Ahmad Farly Akbar; Oki Mardiawan (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. The high level of e-sports activities in West Java & Jakarta can be seen from the number of e-sports events such as the Governor's Cup and the President's Cup of the e-sports industry. In addition, the high interest in e-sports can be seen from the increasing number of participants in the President's Cup from 18 thousand participants in 2018 to 177 thousand participants in 2020 Anggoro. The high working hours that e-sports athletes have, reaching 12-14 hours, may affect the psychological well-being of these athletes, as previous research only discusses general work such as lecturers and nurses, and for e-sports athletes themselves there has been no research on these two variables. The purpose of this study was to determine the relationship between work-life balance and psychological well-being among e-sports athletes in West Java & Jakarta. This research method uses quantitative with cross-sectional design. Data analysis using structural equation modelling (SEM) with respondents in this study total 230 E-sports athletes in West Java. This study uses a psychological scale with Fisher, Bulger, and Smith's (2009) work-life balance measurement instrument adapted by Gunawan (2019) and Ryff's (1989) psychological well-being measurement instrument adapted and revised by Revelia (2018). The results of this study indicate a positive relationship between work-life balance and psychological well-being in West Java and Jakarta e-sports athletes worth (55%). These results indicate that with an increase in Work-life balance, E-sports athletes will experience an increase in Psychological well-being. Abstrak. Tingginya kegiatan e-sports di Jawa Barat & Jakarta dengan dilihat dari banyaknya event e-sports seperti piala gubernur dan Piala Presiden cabang e-sports. Selain itu tingginya peminat e-sports bisa dilihat dari meningkatnya jumlah pendaftar pada piala presiden dari 18 ribu peserta di tahun 2018 menjadi 177 ribu perserta di tahun 2020 Anggoro. Tingginya waktu bekerja yang dimiliki atlet e-sports, yaitu mencapai 12-14 jam dapat mempenagruhi Psychological well-being pada atlet tersebut, dikarenakan penelitian sebelumnya hanya membahas mengenai pekerjaan umum seperti dosen dan perawat, dan untuk atlet e-sports sendiri belum ada penelitian yang dilakukan mengenai kedua variabel ini. Tujuan penelitian ini adalah untuk mengetahui hubungan antara Work-life balance dan Psychological well-being pada atlet E-sports Jawa Barat & Jakarta. Metode penelitian ini menggunakan kuantitatif dengan desain cross-sectional. Analisis data menggunakan Structural Equation Modeling (SEM) dengan responden pada penelitian ini berjumlah sebanyak 230 orang atlet E-Sport di Jawa Barat. Penelitian ini menggunakan skala psikologis dengan alat ukur Work-life balance dari Fisher, Bulger, and Smith, (2009) yang diadaptasi oleh Gunawan (2019), dan alat ukut Psychological well-being dari Ryff (1989) yang telah diadaptasi dan direvisi oleh Revelia (2018). Hasil dari penelitian ini menunjukan adanya hubungan positif antara Work-life balance dan Psychological well-being pada atlet E-sports Jawa Barat & Jakarta senilai (55%). Hasil ini menunjukan bahwa atlet e-sports akan mengalami peningaktan Psychological well-being seiring dengan meningkatnya Work-life balance.